An all-sky luminance and radiance distribution model for built environment studies. (May 2022) - Lou, Siwei; Li, Danny H.W.; Alshaibani, Khalid A.; Xing, Haowei; Li, Zhengrong; Huang, Yu; Xia, Dawei
Abstract: The diffuse radiance and luminance can be anisotropic over the skydome, which is important to the daylight and thermal environments of buildings and the urban areas. This paper proposes a model that can estimate the luminance and radiance distributions over the skydome by the basic global and diffuse irradiance, and the solar altitude measurements/data that are readily accessible for many places over the world. The radiance and luminance are normalized by the horizontal irradiance and illuminance instead of the uncommon zenith radiance and luminance. The approach is developed and tested by the mid-to long-term (a few months to two years) field measurements of several locations with various climates/latitudes, showing a good accuracy when compared to the reference models.